Electromagnetic–Thermal–Mechanical Collaborative Optimized Design of Permanent Magnet Synchronous Motors Used in Concrete Stirring Tankers - Shijun Chen; Xinyu Chen; Cheng Miao; Wei Qian; Songchao Chu; Huwei Chen (International Journal of Rotating Machinery)
The motor involves many factors such as electricity, magnetism, heat, and stress, and thus, electromagnetism, heat, and rotor mechanical structure must be comprehensively considered in motor designing. Here, an electromagnetic–thermal–mechanical structured collaborative optimized design method was proposed for permanent magnet synchronous motors (PMSMs) used in concrete stirring tankers in accordance with the requirements of large torque and low speed. With a water-cooled PMSM with rated power of 47 kW as example, the stator and rotor structures of the PMSM for stirring tankers were optimized on finite element software. Then, the temperature field of the motor and the mechanical structural stress of the rotor were analyzed and designed. The finite element simulation showed the design solution can meet the electromagnetic performance, temperature field performance, and rotor mechanical structural strength required by the motor. Finally, a prototype was made and tested. The experimental results were consistent with the simulation results, which proves the effectiveness and correctness of the motor optimized design method proposed here.